A comparative evaluation of a new automated assay for von Willebrand factor activity. (4th December 2012) - Lawrie, A. S.; Stufano, F.; Canciani, M. T.; Mackie, I. J.; Machin, S. J.; Peyvandi, F.
Summary The ristocetin cofactor assay (VWF:RCo) is the reference method for assessing von Willebrand factor (VWF) activity in the diagnosis of von Willebrand's Disease (VWD). However, the assay suffers from poor reproducibility and sensitivity at low levels of VWF and is labour intensive. We have undertaken an evaluation of a new immunoturbidimetric VWF activity (VWF:Ac) assay (INNOVANCE® VWF Ac. Siemens Healthcare Diagnostics, Marburg, Germany) relative to an established platelet‐based VWF:RCo method. Samples from 50 healthy normal subjects, 80 patients with VWD and 50 samples that exhibited 'HIL' (i.e. Haemolysis, Icterus or Lipaemia) were studied. VWF:Ac, VWF:RCo and VWF:Ag were performed on a CS–analyser (Sysmex UK Ltd, Milton Keynes, UK), all reagents were from Siemens Healthcare Diagnostics. The VWF:Ac assay, gave low intra‐ and inter‐assay imprecision (over a 31‐day period, n = 200 replicate readings) using commercial normal (Mean 96.2 IU dL−1, CV < 3.0%) and pathological (Mean 36.1 IU dL−1, CV < 3.5%) control plasmas. The normal and clinical samples exhibited good correlation between VWF:RCo (range 3–753 IU dL−1) and VWF:Ac (rs = 0.97, P < 0.0001), with a mean bias of 5.6 IU dL−1. Ratios of VWF:Ac and VWF:RCo to VWF:Ag in the VWD samples were comparable, although VWF:Ac had a superior lower level of detection to that of VWF:RCo (3% and 5% respectively). A subset (n = 97) of VWD and HIL samples were analysed for VWF:Ac at two different dilutions to assess the effect on relative potency, no significant difference was observed (P = 0.111). The INNOVANCE® VWF Ac assay was shown to be reliable and precise.